Can Citizen Projects Make Pancasila Education Measurable? Evidence Map Based on Pancasila Student Profile Stages - Eko Priyanto; Nadarajan Thambu; Ani Kusbandiyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study investigates how the Project Citizen model strengthens the Pancasila Student Profile (PPP) in Pancasila Education at MTs Muhammadiyah Purwokerto, Indonesia. A qualitative case study was conducted involving a Pancasila Education teacher and MTs students engaged in a full Project Citizen cycle. Data were collected from participatory classroom observations across the stages of Project Citizen, in-depth semi-structured interviews with the teacher and selected students, and document analysis of student project artifacts (e.g., issue analyses, evidence summaries, policy drafts, presentation materials, and reflective notes). Data were analyzed through iterative thematic coding aligned with the six PPP dimensions and emergent codes, strengthened by cross-source triangulation and an explicit evidence-density rubric. PPP development was stage-specific: critical reasoning intensified during problem identification and inquiry; collaboration and creativity peaked during deliberation and policy proposal design; global diversity became salient during public presentation; and moral integrity consolidated through reflection and evaluation. Co-occurrence analysis further indicated strong linkages among critical reasoning, collaboration, and moral integrity, suggesting PPP operates as an interconnected competency configuration rather than isolated outcomes. Project Citizen operationalizes PPP through evidence-informed civic inquiry, deliberative collaboration, and structured ethical reflection within Pancasila Education.